Reverse Share-Tenancy and Marshallian Inefficiency: Bargaining Power of Landowners and the Sharecroppers' Productivity - Hosaena H. Ghebru; Stein T. Holden (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2012)
Making use of a unique tenant-landlord matched data from the Tigray region of Ethiopia, we are able to show how strategic response of tenants - to varying economic and tenure security status of the landlords - is important in explaining productivity differentials of sharecroppers. The results show that sharecroppers yield are significantly lower on plots leased from landlords who are non-kin; female; with lower income generating opportunity; and tenure insecure households, than on plots leased from landlords with contrasting characteristics. While, on aggregate, the result shows no significant efficiency loss on kin-operated sharecropped plots, a more decomposed analyses indicate strong evidences of Marshallian inefficiency on kin-operated plots leased from landlords with weaker bargaining power and higher tenure insecurity. This study, thus, shows how failure to control for such heterogeneity of landowners' characteristics can explain the lack of clarity in the existing empirical literature on the extent of moral hazard problems in sharecropping contracts.
Keywords: D01; O13; O18; Q12; Q15; 330; Marshallian inefficiency; kinship; matching; Reverse-Share-Tenancy; Ethiopia